Absence of increased genomic variants in the cyanobacterium Chroococcidiopsis exposed to Mars-like conditions outside the space station - Alessandro Napoli; Diego Micheletti; Massimo Pindo; Simone Larger; Alessandro Cestaro; Jean-Pierre de Vera; Daniela Billi (Scientific Reports, 2022)
Abstract Despite the increasing interest in using microbial-based technologies to support human space exploration, many unknowns remain not only on bioprocesses but also on microbial survivability and genetic stability under non-Earth conditions. Here the desert cyanobacterium Chroococcidiopsis sp. CCMEE 029 was investigated for robustness of the repair capability of DNA lesions accumulated under Mars-like conditions (UV radiation and atmosphere) simulated in low Earth orbit using the EXPOSE-R2 facility installed outside the International Space Station. Genomic alterations were determined in a space-derivate of Chroococcidiopsis sp. CCMEE 029 obtained upon reactivation on Earth of the space-exposed cells. Comparative analysis of whole-genome sequences showed no increased variant numbers in the space-derivate compared to triplicates of the reference strain maintained on the ground. This result advanced cyanobacteria-based technologies to support human space exploration.